(untitled) (Географический вестник=Geographical bulletin, 2017)
A greenhouse pot experiment was conducted for investigating the capability of a grass (annual ryegrass), a legume (summer vetch), and a crucifer (white mustard) to grow in a soil from a former coal gasification site and promote the biodegradation of petrol hydrocarbons (PHCs). Soil concentrations of 1517 mg kg-1 of total petrol hydrocarbons (TPHs), including 71.4 mg kg-1 of total US EPA priority polycyclic aromatic hydrocarbons (TPAHs) have caused a significant (P<0.05) reduction in shoot and root yields by more than 50%. Abundance and bacterial community composition in soil and rhizosphere were distinctly altered by the PHC contaminants and also depended on crop species and age. After 95 days, 68.7% of initial TPH amounts and 59% of the TPAHs had disappeared from unplanted soil. The removal of PHCs was fostered in soil planted to mustard and vetch reaching final TPH concentrations that were 15.6% and 12%, respectively, lower than in unplanted soil. Mustard and vetch elicited the greatest degradative root activities and sustained particularly great populations of rhizosphere bacteria that are known hydrocarbon degraders. None of the crops aided the biodegradation of TPAHs in soil.